Actualización de las especies del género Macrodactylus Dejean (Coleoptera: Melolonthinae: Macrodactylini) para el estado de Puebla, México - Aragón-Sánchez, Miguel; Aragón García, Agustín; Arce-Pérez, Roberto; Pérez Torres, Betzabeth Cecilia; Cuate-Mozo, Víctor Alfonzo; López-Olguín, Jesús Francisco (Instituto de Ecología, A.C., 2021)
The state of Puebla, Mexico, ranks fifth in species richness of the genus Macrodactylus with nine species. Through the revision of scientific collections and field work, the number of species was actualized to ten, with Macrodactylus lineatocollis Bates 1887, as a new state registry. Maps are presented with their territorial distribution, which are related to the variables of mean annual temperature and humidity ranges. Biological comments are made for each species and a dichotomous key is presented for the identification of the species present in the state of Puebla.